Changes in physical activity by context and residential greenness among recent retirees: Longitudinal GPS and accelerometer study. (January 2022) - Pasanen, S.; Halonen, J.I.; Gonzales-Inca, C.; Pentti, J.; Vahtera, J.; Kestens, Y.; Thierry, B.; Brondeel, R.; Leskinen, T.; Stenholm, S.
Abstract: This study examined the changes in accelerometer-measured physical activity by GPS-measured contexts among Finnish retirees (n = 45 (537 measurement days)) participating in a physical activity intervention. We also assessed whether residential greenness, measured with Normalized Difference Vegetation Index, moderated the changes. Moderate-to-vigorous physical activity (MVPA) increased at home by 7 min/day, (P < 0.001) and during active travel by 5 min/day (P = 0.03). The participants with the highest vs. lowest greenness had 25 min/day greater increase in MVPA over the follow-up (P for Time*Greenness interaction = 0.04). In conclusion, retirees participating in the intervention increased their MVPA both at home and in active travel, and more so if they lived in a greener area. Highlights: We examined changes in physical activity in different contexts among retirees. Waist-worn devices were used to collect combined physical activity and GPS data. Light PA occurring during active travel decreased during 1-year follow-up. MVPA occurring at home and during active travel increased during 1-year follow-up. Higher greenness was associated with greater increase in MVPA over 1-year follow-up.